Adsorption design for wastewater treatment - Cooney, David O. (CRC Press LLC, 1999)
Adsorption: it's the most important method for removing organic contaminants from wastewater streams. Students and professionals alike in the fields of water/wastewater treatment and environmental engineering have expressed tremendous interest in learning and understanding adsorption processes.Adsorption Design for Wastewater Treatment fulfills the need for a true textbook on this increasingly important subject . From the basics of the adsorption process to specifics on system design, this overview serves a dual purpose: study manual and design guide.Straightforward explanations and illustrations make Adsorption Design for Wastewater Treatment ideal for junior, senior and graduate-level university courses. Practicing engineers will find the book especially useful for accurate, direct advice on designing batch and fixed-bed adsorption systems.Contaminant removal will be an ever-present challenge to environmental engineers. Gain a clear understanding of one of the most important cleanup methods with Adsorption Design for Wastewater Treatment.